Opportunistic Community Acquired Pneumonia Due to Rare Pathogen Serratia Plymuthica - Peetam Singh; Anita Pandey (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Serratia is a Gram-negative rod-shaped bacteria belonging to the order Enterobacterales, comprising Serratia marcescens as the most commonly isolated pathogenic and representative species of the genus. Most of these non-marcescens Serratia species were usually considered as non-pathogenic and only a few of them have been rarely reported in case reports causing opportunistic infections. Serratia plymuthica was previously considered as an environmental contaminant and commonly isolated from various plants including mushrooms and their human pathogenic potential was not clearly understood. Serratia plymuthica has rarely been reported globally and is considered an opportunistic pathogen infecting immunocompromised subjects. Only a few case reports are available documenting the clinical significance of Serratia plymuthica causing various manifestations. We reported a case of community-acquired pneumonia caused by Serratia plymuthica in an immunocompromised patient from a tertiary care teaching institute in Uttar Pradesh, India.